Quantification of ecosystem services from mangrove silvofishery - E. Sumarga; D. Rosleine; G.B. Hutajulu; R.P. Plaurint; Tsabita .; M. Basyuni; S.H. Larekeng; M.F. Taqiyudin; N.N. Shohihah; H. Ali (Global Journal of Environmental Science and Management)
BACKROUND AND OBJECTIVES: Mangrove silvofishery, a unique system that combine aquaculture with mangrove forests, presents a promising sustainable solution for Indonesia's coastal communities. However, in order to achieve broad implementation, it is essential to bridge the existing knowledge gap concerning the economic and environmental benefits associated with it. The aim of this study was to assess the four primary services rendered by the Blanakan mangrove silvofishery area in Subang District, West Java: carbon sequestration, fisheries productivity, nature-based tourism, and bird sanctuary.METHODS: Carbon storage was calculated by conducting vegetation surveys and utilizing allometric equations, which took into account both aboveground and belowground biomass. During the vegetation survey, data regarding the types of mangrove plants and the diameter of each tree at breast height was gathered. To quantify fisheries production, interviews were conducted with area managers and pond farmers who are engaged in silvofishery practices within the region. The point-count method was used to inventory the diversity of bird species. The analysis of natural tourism services encompassed an examination of visitor statistics, the state of the mangroves as a popular tourist destination, and the range of tourist activities available.FINDINGS: The study revealed the high capacity of the mangrove stands at the study location for carbon storage, with an estimated 137.9 tonnes carbon per hectare aboveground and 79 tonnes carbon per hectare belowground. Local communities actively engage in silvofishery practices within the Blanakan mangroves, cultivating fish and shrimp, with an average annual income of around 1,513 United States dollar per hectare. 2. The natural beauty of the Blanakan mangrove area attracts tourists with its diverse ecosystem and opportunities to see crocodile breeding facilities. Visitor numbers vary, averaging around 128 people per month until mid-2023. The Blanakan mangroves are home to a total of 23 bird species, contributing to a species diversity index of 2.1. Two species with significant conservation value were found: the critically endangered Javan Blue-banded Kingfisher (Alcedo euryzona) and the vulnerable Black-capped Kingfisher (Halcyon pileata).CONCLUSION: The results emphasize the importance of advancing and advocating for silvofishery as a primary alternative in Indonesia's mangrove conservation and rehabilitation initiatives, enhancing coastal environmental management. Community engagement is of utmost importance in the successful development of mangrove silvofishery, as it aims to tackle the issue of limited awareness and participation among the local community.